Ready made : how to make (almost) everything : a do-it-yourself primer. - Berger, Shoshana, ....- (London : Thames and Hudson, 2006)
You need this book. As the stuff of life piles up and things spin out of control, we could all use a little help. These never-before-seen designs and how-tos are full of surprise and wonder. Learn how to turn everyday objects into spellbinding inventions to give away to friends or keep for yourself. Our simple self-improvement techniques will make you smarter, better-looking, and more well-adjusted.